INFLUENCE OF INCORPORATED DIGESTATE COMPOSITIONAL PARAMETERS ON CO2 EMISSION AND CARBON TURNOVER PROCESSES IN SOIL - S. Sunuwar (Journal CleanWAS)
Anaerobic digestion is considered as the reliable source of renewable energy which provides two valuable products i.e., biogas and digestate slurry. Biogas, an alternative energy, is one of the important forms of clean energy whereas digestate has multipurpose usage, including organic fertilizer in many parts of the world. The compositional parameters such as C:N, cellulose and lignin contents of digestate are important indicators of their qualities that indicate the biodegradability status as well as importance in CO2 evolution and Carbon (C) turnover process. In a 35-day long incubation study, The six different feedstock sources digestate slurry was applied in silty loam soil to explore the C turnover process that were arranged in a completely randomized block design. Microbial respiration (in terms of CO2 respired) were measured to understand the biodegradability of different digestates. We found CO2 evolution was negatively correlated with C:N of digestates. The digestates releasing more carbon dioxide evolution may not be suitable manure but may be utilized by mixing with higher recalcitrance containing organic matter.